The silence of numbers: Why Goiás and Ceará show such different patterns in Hepatitis notifications (Research, Society and Development, 2025)
The present article aims to analyze the temporal evolution of confirmed hepatitis cases in Goiás, the Central Region of Goiás and Ceará, using TABNET DATASUS data to identify patterns of occurrence and annual variations. The study examines the evolution of confirmed cases in these locations through historical series, shows long periods of minimal notifications that do not represent the real circulation of hepatotropic viruses in the country, identifies important oscillations and expressive increases from 2022 onward, and suggests greater sensitivity of surveillance systems after the reorganization of health services and the expansion of testing in the post pandemic period. The regional differences observed highlight inequalities in detection and reporting capacity, indicate underreporting as a central factor to explain the epidemiological behavior found, and point to the need to strengthen reporting flows, qualify professionals and expand access to testing to improve surveillance and guide prevention and control actions for viral hepatitis in Brazil.